Dental Caries Status in HIV - Infected Patients at Dong Da General Hospital, Hanoi - Phuong, Vu Le; Thi Ngoc Anh, Tran; Hung, Le; Tuan Hiep, Hoang (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Abstract: Background and Rationale: Human Immunodeficiency Virus (HIV) compromises the immune system, increasing vulnerability to opportunistic infections. While Antiretroviral Therapy (ART) improves survival, both HIV and ART side effects often cause salivary gland hypofunction and xerostomia. This reduced salivary protection accelerates bacterial proliferation, making dental caries a frequent, yet under-researched, complication compared to mucosal or periodontal lesions. Untreated caries leads to pulpitis and tooth loss, severely impacting patients' nutrition and quality of life. This study aimed to investigate the prevalence and epidemiological characteristics of dental caries among HIV/AIDS patients at Dong Da General Hospital, Hanoi. Methods: A cross-sectional descriptive study was conducted from February to September 2022 on 110 outpatient HIV/AIDS patients (aged ≥18) at the Department of Infectious Diseases. Data collection included structured questionnaires for sociodemographic data, medical record reviews for immune status (CD4 counts), and clinical examinations to assess dental caries, calculate the DMFT (Decayed, Missing, Filled Teeth) index, and analyze relationships with paraclinical markers. Results: Results revealed a high dental disease burden: 71.8% of participants had dental caries, and 52.7% experienced tooth loss. Patients averaged 2.28 ± 2.1 decayed teeth and 1.65 ± 2.44 missing teeth. A significant statistical association was found between dental caries severity (and DMFT index) and CD4 cell counts, confirming lower immune function correlates with poorer oral health. Additionally, missing teeth prevalence was significantly associated with older age groups. However, active caries prevalence and the DMFT index showed no significant correlation with gender or age alone. Conclusion: These findings underscore the urgent need to integrate comprehensive oral health management, including regular dental screenings and tailored preventive interventions, into standard HIV care protocols to mitigate the high dental disease burden and improve patients' overall quality of life. Keywords: HIV, dental caries, missing teeth, DMFT, CD4 cell count.